CRIMINAL LEGISLATION IN BOSNIA AND HERZEGOVINA ON TERRORISM (Heritage, 2022)
In this paper, we focus on terrorism through the criminal legislation of Bosnia and Herzegovina. In the existing scientific fund, professional literature, various organizations, institutions, political entities, there is not a sufficient degree of agreement to be able to form a court that there is, in general, a generally accepted definition of terrorism. On the other hand, given the various activities and actions, results, effects and consequences of terrorist organizations and terrorists, we must state that there is a very high degree of agreement, that terrorism is one of the biggest security and security threats today. The growing increase in terrorist actions and threats has led to the implementation of new legislative norms in order to better counter terrorism. Organized crime at the international level and terrorist activities increasingly require the connection of states, international organizations through Conventions, Resolutions or Laws. Terrorism acts ambivalently and as a threat to the stability of society, states and their development on a global level. The expansion of terrorism over time has surprised many organizations, institutions, whose goal is to preserve security, where the need for reforms has arisen. Through the laws in Bosnia and Herzegovina, we will see how the legislator has solved the issue of terrorism and what are the consequences for those who do not adhere to them.
Keywords: Bosnia and Herzegovina, Republika Srpska, terrorism, legislation, reforms, Convention, penalties.